3D Model Reconstruction Using Gan and 2.5D Sketches from 2D Image - Quach Thi Bich Nhuong; Pham Dinh Sac; Nguyen Minh Nhut; Hien Thanh Le (Jurnal Teknologi Informasi dan Pendidikan, 2022)
In the current 4.0 era, many fields such as medicine, cinema, architecture, etc. often use 3D models to visualize objects. However, there is not always enough information or equipment to build a 3D model. Another approach is to take multiple 2D images and convert to 3D shapes. This method requires information on images taken of objects at different angles. To get around this, we use a 2.5D sketch as an intermediary when going from 2D to 3D. A 2D photo is easier to create a 2.5D sketch than to convert directly to a 3D shape. In this paper, we propose a model consisting of three modules: The first is converting from 2D image to 2.5D sketch. The second is to go from a 2.5D sketch to a 3D shape. Finally, refine the newly created 3D shape. Experiments on the ShapeNet Core55 dataset show that our model gives better results than traditional models